Relation between obesidade and calcium a boarding of carried through studies - Crisóstomo, Nadiana Lopes (2012)
The obesity is one of the oldest metabolic riots. Currently there are more than a billion of over weights adults all over ther world, and at least 300 million of them are obeses. In Brazil, these figure has been increasing lately. The studying of obesity and its evolution, recent works have investigated the function of calcium in the prevention and treatment of obesity. This work has as objective to analyze the relation between obesity and calcium, approaching a general vision of fulfilled studies relating the ingestion of calcium in the prevention and/or treatment of the obesity. This works show a tendency in the increase of obesity, presenting difficulties in slimming and its recurrent maintenance. Researchers had found in calcium a good result. Presented hypotheses shows that the calcium modifies the absorption of fat through the organism. Studies had esteemed the participation of food in its ingestion and present milk and its essential derivatives for the increase of the calcium levels in the organism. In these same works, patients who were submitted to diets in order to loose weight, with high calcium texts, displayed reduction in the corporeal balance. Patients who were submitted to a normal diet evidenced that this dietary source contributes a lot to the absorption of calcium. It was concluded that is necessary planting of information and new studies. Milk, its derivatives and other kind of food do not work as a “magical pill”, and the energy balance remains as basic cause of obesity and consequent metabolic alterations.